The effect of Google Classroom assisted STEM approach on students’ creative thinking skills - Betti Widiasari; Nukhbatul Bidayati Haka; Nur Hidayah; Akbar Handoko; Aulia Novitasari (Assimilation: Indonesian Journal of Biology Education, 2022)
Low creative thinking skills, the approach used in learning has not facilitated students to understand problems and express many ideas. The purpose of this study was to determine the effect of the Google Classroom-assisted STEM approach on creative thinking skills. This study used a quantitative research type with Quasi-Experimental Design. The population in this study were all students of class VIII SMP Negeri 20 Bandar Lampung, with a sampling technique that is cluster random sampling obtained Class G as the experimental class and Class H as the control class. The data collection technique used a test instrument in the form of an essay test to measure students' creative thinking skills. Hypothesis testing was using the Independent Sample T-test which was preceded by a pre-requisite test for normality and homogeneity of the data. The results of the t-test hypothesis test obtained a significance of 0.00 0.05, meaning that H0 is rejected so that it can be concluded that the STEM approach assisted by Google Classroom has an effect on students' creative thinking, with the acquisition of each indicator: 79.7% originality indicator, 80,7% flexibility,82% elaboration, and 81.2% fluency.This increase can be seen from the impact on students that becoming more enthusiastic by motivating each other among friends through creative thinking so that they are able to make decisions and solve problems well.